2023
DOI: 10.1186/s42506-022-00123-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of safe injection awareness and practices among healthcare providers at primary health care facilities

Abstract: Background Unsafe injection necessitates some preventive steps including promoting and assuring the execution of safe injection administration and waste disposal methods. The present study aimed to assess the awareness and practices of safe injection among health care providers working at all primary health care (PHC) facilities in Fayoum governorate, Egypt. Also, it assessed the awareness, readiness, and response related to needle stick injuries (NSIs). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Depending on Tables (3-2) and (3-3) The overall evaluation of healthcare provider adherence to safe injection practice was fair. this result matched with the study finding of Ali and Eldessouki, (2022) that represented the majority of study participants had a good awareness about safe injection practices 2 . as well as these findings linked with the result of Anwar et al, (2019) and Birhanu et al, (2019) they found in their study the majority of study sample practices and awareness regarding safe injection was good 3,4 , in addition to Van Tuong, et al, 2017 andIsmail, et al, (2014), they emphases in their study that the most of study subject have a high level of knowledge related to the safety of injection procedure 6,7 , despite Zakar, et al, (2013), the stated in their study that the most of study respondent were not scientifically qualified or trained among providing parenteral medication.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…Depending on Tables (3-2) and (3-3) The overall evaluation of healthcare provider adherence to safe injection practice was fair. this result matched with the study finding of Ali and Eldessouki, (2022) that represented the majority of study participants had a good awareness about safe injection practices 2 . as well as these findings linked with the result of Anwar et al, (2019) and Birhanu et al, (2019) they found in their study the majority of study sample practices and awareness regarding safe injection was good 3,4 , in addition to Van Tuong, et al, 2017 andIsmail, et al, (2014), they emphases in their study that the most of study subject have a high level of knowledge related to the safety of injection procedure 6,7 , despite Zakar, et al, (2013), the stated in their study that the most of study respondent were not scientifically qualified or trained among providing parenteral medication.…”
Section: Methodssupporting
confidence: 89%
“…Ali and Eldessouki, (2022) they reported in their study there is no significant association between ( living in urban or rural residential areas and years of experience) and injection safety 2 . Moreover, Van Tuong, et al, 2017 reported in their study there is a significant relationship between safe injection practices and (young age nurses, years of experience <10 and training in correct injection technique) but no significant relation with nurses qualifications 7 .…”
Section: Resultsmentioning
confidence: 82%
“…It is a simple and low-cost action that reduces the rates of acquisition of pathogens on hands significantly (15) . While, discarding single use injection devices after use was 100% implemented, which is comparable to the results of Ali and Eldessouki (16) in which immediate disposal of used needles was 76.2% in observed injections, and different from the study of Ismail et al (17) who found safe needle disposal in only 47.5% of the healthcare workers.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, our data revealed statistically significant differences in levels of awareness and practice across various categories. Ali and Eldessouki also reported 76.2% of immediate disposal of used needles [3] . This study is one of the few that included nurses and investigated differences in awareness and practice, additional research is recommended to back up the findings and explore different paths for achieving optimal compliance and preventing serious consequences.…”
Section: Discussionmentioning
confidence: 98%
“…The Safe Injection Global Network (SIGN) describes safe injection practices as a collection of measures aiming to promote safe patient injection behaviour while not jeopardizing the healthcare provider or the broader community [1,2] . Unsafe injection procedures are widespread in developing nations' healthcare institutions, contributing to a number of preventable healthcare-related problems despite significant attempts to limit the frequency of harmful injections in poor countries [3,4] . In the year 2000, improper injection practices caused estimated 20 million new hepatitis B virus (HBV) infections, 2 million new hepatitis C virus (HCV) infections, and 250,000 new human immunodeficiency virus (HIV) infections [5] .…”
Section: Introductionmentioning
confidence: 99%